Posttranscriptional and posttranslational control of enolase expression in the facultative Crassulacean acid metabolism plant Mesembryanthemum Crystallinum L. - Forsthoefel, N R (1995)
During the induction of Crassulacean acid and metabolism by environmental stresses in the common ice plant (Mesembryanthemum crystallinum L.), enzyme activities involved in glycolysis and gluconeogenesis, including enolase (2-phospho-D-glycerate hydrolase), increase significantly. In this study, we describe two nearly identical cDNA clones (Pgh1a and Pgh1b) encoding enolase from the common ice plant. This cytoplasmically localized enzyme is encoded by a gene family of at least two members. The polypeptides encoded by these cDNAs share a high degree of amino acid sequence identity (86.7-88.3%) with other higher plant enolases. Enolase activity increased more than 4-fold in leaves during salt stress. This increase was accompanied by a dramatic increase in Pgh1 transcription rate and the accumulation of enolase transcripts in leaves. Pgh1 transcript levels also increased in leaves in response to low temperature, drought, and anaerobic stress conditions and upon treatment of unstressed plants with the plant growth regulators abscisic acid and 6-benzylaminopurine. In roots, enolase transcripts increased in abundance in response to salt, low and high temperature, and anaerobic stresses. Surprisingly, we observed no increase in enolase protein levels, despite the increased levels of mRNA and enzyme activity during salt stress. The stress-induced increase in enolase activity is therefore due to posttranslational regulation of steady-state enzyme pools. Our results demonstrate that the stress-induced shift to Crassulacean acid metabolism in the ice plant involves complex regulatory control mechanisms that operate at the transcriptional, posttranscriptional, and postranslational levels.